Development of Mathematics Teaching Materials Based on the Realistic Mathematics Approach (PMR) to Improve the Mathematical Reasoning and Representation Ability of Class VII Students of SMP Muhammadiyah 47 Medan Sunggal - Ibnu Raash Aleslami; Ani Minarni; KMS. M. Amin Fauzi (BIRCU, 2021)
This study aims to analyze the validity and effectiveness of teaching materials developed based on a realistic mathematical approach in improving students 'mathematical reasoning and representation abilities, to analyze the increase in students' reasoning skills and mathematical representation abilities taught using teaching materials based on realistic mathematical approaches. The data were obtained through the validation sheet of teaching materials, observation sheets, student response questionnaires, mathematical reasoning ability test instruments and mathematical representation ability tests. This study uses a 4-D development model Thiagarajan, Semmel and Semmel by developing teaching materials with a realistic mathematical approach. Based on the results of the validation, the total average value of the RPP validity was 4.81, the student books were 4.83 and the LKPD was 4.85, the students' mathematical reasoning ability tests and the mathematical representation ability tests were in the valid category. Classical mastery of learning reaches 90.62% which has met the completeness criteria, namely ≥85% of students have reached the KKM. The increase in students' mathematical reasoning abilities using teaching materials based on a realistic mathematical approach on fraction material seen from N-Gain in the first trial and second trial has increased from 0.36 to 0.50 meaning that it is in the medium category. As well as an increase in the ability of students' mathematical representation using teaching materials based on a realistic mathematical approach on fraction material seen from N-Gain in the first trial and second trial, it increased from 0.43 to 0.50, meaning that it was in the medium category.